STUB1/CHIP mutations cause Gordon Holmes syndrome as part of a widespread multisystemic neurodegeneration: evidence from four novel mutations - Hayer, Stefanie Nicole; Deconinck, Tine; Bender, Benjamin; Smets, Katrien; Züchner, Stephan; Reich, Selina; Schöls, Ludger; Schüle, Rebecca; De Jonghe, Peter; Baets, Jonathan; Synofzik, Matthis (Orphanet journal of rare diseases, 2017)
Background CHIP, the protein encoded by STUB1 , is a central component of cellular protein homeostasis and interacts with several key proteins involved in the pathogenesis of manifold neurodegenerative diseases. This gives rise to the hypothesis that mutations in STUB1 might cause a far more multisystemic neurodegenerative phenotype than the previously reported cerebellar ataxia syndrome. Methods Whole exome sequencing data-sets from n = 87 index subjects of two ataxia cohorts were screened for individuals with STUB1 mutations. In-depth phenotyping by clinical evaluation and neuroimaging was performed in mutation carriers. Results We identified four novel STUB1 mutations in three affected subjects from two index families (frequency 2/87 = 2.3%). All three subjects presented with a severe multisystemic phenotype including severe dementia, spastic tetraparesis, epilepsy, and autonomic dysfunction in addition to cerebellar ataxia, plus hypogonadism in one index patient. Diffusion tensor imaging revealed degeneration of manifold supra- and infratentorial tracts. Conclusions Our findings provide clinical and imaging support for the notion that CHIP is a crucial converging point of manifold neurodegenerative processes, corresponding with its universal biological function in neurodegeneration. Further, our data reveal the second STUB1 family with ataxia plus hypogonadism reported so far, demonstrating that Gordon Holmes syndrome is indeed a recurrent manifestation of STUB1 . However, it does not present in isolation, but as part of a broad multisystemic neurodegenerative process. This supports the notion that STUB1 disease should be conceptualized not by historical or clinical syndromic names, but as a variable multisystemic disease defined by disturbed function of the underlying STUB1 gene, which translates into a multidimensional gradual spectrum of variably associated clinical signs and symptoms.